Integrated Analysis of Basic Helix Loop Helix Transcription Factor Family and Targeted Terpenoids Reveals Candidate AarbHLH Genes Involved in Terpenoid Biosynthesis in Artemisia argyi - Yi, Xiaozhe; Wang, Xingwen; Wu, Lan; Wang, Mengyue; Yang, Liu; Liu, Xia; Chen, Shilin; Shi, Yuhua (Frontiers in Plant Science, 2022)
Artemisia argyi is a valuable traditional medicinal plant in Asia. The essential oil from its leaves is rich in terpenoids and has been used to enhance health and well-being. In China, the market scale of industries related to A. argyi has attained tens of billions of Chinese Yuan. The basic Helix Loop Helix (bHLH) famlily is one of the largest transcription factors (TFs) in plants that plays crucial roles in diverse biological processes and is essential regulatory component of terpenoid biosynthesis. However, the bHLH TFs and their regulation roles in A. argyi are still unknown. Here, Fifty-three AarbHLH genes were identified from the transcriptome of A. argyi and were classified into 15 subfamilies based on the classification of bHLH proteins in Arabidopsis thaliana. The MEME analysis of showed that the conserved motif 1 and motif 2 constituted the most conserved domains of bHLH distributed in AarbHLH proteins. Additionally, an integrated analysis of expression profiles of AarbHLH genes and the contents of targeted terpenoids in different tissues group and JA-treated group were performed. Eleven up-regulated AarbHLHs and one down-regulated AarbHLHs were screened as candidate genes that may participate in the regulation of terpenoid biosynthesis (named TPS-AarbHLHs). Correlation analysis between gene expression and terpenoid contents indicated that the gene expression of 12 TPS-AarbHLHs were significantly correlated with the content changes of 1,8-cineole or β-caryophyllene. Protein-protein interaction networks further illustrated that these TPS-AarbHLHs might be involved in terpenoid biosynthesis in A. argyi. This finding provides a basis to further investigate the regulation mechanism of AarbHLH genes in terpenoid biosynthesis, and will be helpful to improve the quality of A. argyi.